1996
DOI: 10.1111/j.1432-1033.1996.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of an Insect Aquaporin

Abstract: We previously described the structural organization of P25, a member of the major-intrinsic-protein family found in the digestive tract of homopteran sap-sucking insects [Beuron, F., Le Cahérec, F., Guillam, M. T., Cavalier, A., Garret, A., Tassan, J. P., Delamarche, C., Schultz, P., Mallouh, V., Rolland, J. P., Hubert, J.F., Gouranton, J. & Thomas, D. (1995) J. Biol. Chem. 270, 17414-17422]. We demonstrated, by means of introducing P25 tetramers into the membranes of Xenopus oocytes, that this protein exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 38 publications
3
80
0
Order By: Relevance
“…Aquaporins have been divided into two types: one subgroup is highly selective for the passage of water, and the other subgroup transports water as well as small neutral solutes such as glycerol. Experimental studies on the transport properties are facilitated by the fact that the water-conducting properties of these channels are inhibited by mercuric chloride, HgCl 2 (Preston et al, 1992), as also shown for an insect aquaporin (Le Caherec et al 1996b). This inhibition apparently is due to binding of the mercury molecule with the aquaporin protein in a narrow part of the pore, so occluding the aqueous pathway (Murata et al 2000).…”
Section: Introductionmentioning
confidence: 92%
“…Aquaporins have been divided into two types: one subgroup is highly selective for the passage of water, and the other subgroup transports water as well as small neutral solutes such as glycerol. Experimental studies on the transport properties are facilitated by the fact that the water-conducting properties of these channels are inhibited by mercuric chloride, HgCl 2 (Preston et al, 1992), as also shown for an insect aquaporin (Le Caherec et al 1996b). This inhibition apparently is due to binding of the mercury molecule with the aquaporin protein in a narrow part of the pore, so occluding the aqueous pathway (Murata et al 2000).…”
Section: Introductionmentioning
confidence: 92%
“…Research of aquaporins in Cicadella viridis began with the filter chamber [18], a structure, built by highly specialized epithelial cells, localized in the digestive tract. It is responsible for the rapid transport of water from the initial midgut, to the terminal midgut and Malpighian tubules.…”
Section: Aquaporin Localized In Homopteran Sap-sucking Insect Cicadelmentioning
confidence: 99%
“…Because these cysteines are localized near the transmembrane domains, access to them by ions is difficult. Therefore, a higher concentration of ions is most likely necessary to inhibit water permeability [18] (Fig. 3).…”
Section: Aquaporin Localized In Homopteran Sap-sucking Insect Cicadelmentioning
confidence: 99%
See 2 more Smart Citations